The Bahamas : Staff Report for the 1999 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 1999)
This 1999 Article IV Consultation highlights that real GDP growth for The Bahamas accelerated from less than 1 percent a year in 1994-95 to 4 percent in 1996, but slowed somewhat in 1997-98 as construction work on a second phase of tourism projects led to a decline in the number of available hotel rooms and in tourist arrivals. Following the completion of the expansion projects in November-December 1998, tourist arrivals rose sharply in the first quarter of 1999.